O sistema opioide contribui para o efeito do tipo antidepressivo do disseleneto de m-trifluormetil-difenila em camundongos - Rosa, Suzan Gonçalves (2018)
Depression is a mental disorder with complex pathophysiology and characterized by multiple symptoms, which makes it difficult to treat this disease. In the last decades, the opioid system has become the focus of depression researches, given that this system has an important regulatory effect on mood. However, the opioids use in the clinic is limited by the development of tolerance and dependence after repeated administration. The organoselenium compound m-trifluoromethyl-diphenyl diselenide (m-CF3-PhSe)2 elicits antidepressant-like effect in animal models through different action targets, including the opioid system. Thus, the main objective of this thesis was to evaluate the opioid system contribution to the pharmacological effect of the organic compound of selenium (m-CF3-PhSe)2 in models of depression in swiss male mice. The results of article 1 demonstrated the (m-CF3-PhSe)2 antidepressant-like effect on the forced swimming test (FST) and the contribution of each opioid receptor to this effect through the use of selective antagonists of these receptors, suggesting that μ and δ receptors activation and κ-receptor blockade are involved in the antidepressant-like action of the compound. In addition, article 1 revealed the antidepressant-like effect of acute or repeated administration of (m-CF3-PhSe)2 on the FST and the modified tail suspension test (TST). In the modified TST, the involvement of the opioid system in the antidepressant-like action of the compound was demonstrated by the increase of behaviors characteristic of opioid system modulation. The article 1 also demonstrated that repeated administration of (m-CF3-PhSe)2 neither induce tolerance in the FST nor physical signs of naloxone-induced withdrawal and did not alter systemic toxicity parameters. Based on these results, it was investigated the molecular mechanisms by which the opioid system contributes to the antidepressant-like effect of (m- CF3-PhSe)2. For this, stress-induced depression models were carried out, given that the opioid system is involved in the different responses to stress. The article 2 revealed that one or repeated forced swimming stress (FSS) exposures induced depressant-like behavior and affected the prefrontal cortical opioid receptor levels of mice. In this study, (m-CF3-PhSe)2 was effective against depressant-like symptoms induced by repeated FSS in the FST, the TST and the splash test through of μ and κ receptor levels regulation. Therefore, the (m-CF3- PhSe)2 effect was investigated in a more severe and prolonged stress model in the article 3. In this study, social defeat stress (SDS) induced social aversion and altered the levels of the three opioid receptors types in the prefrontal cortex of susceptible mice. (m-CF3-PhSe)2 was effective against these changes, promoting resilience to SDS and increasing the natural sociability among mice. Together, the results of this thesis contributes to the understanding of the opioid mechanisms involved in the antidepressant-like effect of (m-CF3-PhSe)2 and indicates that this compound may be an therapeutic alternative for the treatment of depression.